The Position of Islamic Jurisprudence and International Law on Armed Resistance The Palestinian Armed Resistance as a Model - Halimi mohamed dhiya elhak Halimi mohamed dhiya elhak (Journal of Science and Knowledge Horizons, 2025)
This research paper aims to clarify the positions of Islamic jurisprudence and international law regarding armed resistance in general, and Palestinian armed resistance in particular, especially in light of the ongoing debate about the legitimacy of this resistance in achieving its goals, particularly after the Al-Aqsa Flood battle and its significant outcomes on all levels. One of the key findings is the positive stance of both Islamic jurisprudence and international law towards armed resistance in affirming the right of peoples to defend themselves and their right to self-determination, using various means including the use of armed force. From the perspective of Islamic jurisprudence, what armed resistance, including Palestinian resistance, is doing is considered a form of defensive jihad that is mandated by Islamic law for those who meet its conditions. From the perspective of international law, various international texts enshrine and support this right, affirming its legitimacy in the pursuit of freedom.